Patient’s Information Toward Some Modifiable Risk Factors of Ischemic Heart Disease - Omar Sharif, Bayan; Hamad Rasul, Aras; Ibrahim Mahmud, Osman; Nuri Abdulla, Farman (Kurdistan Journal of Applied Research, 2020)
Ischemic heart disease (IHD), , is the condition of heart problems, caused by narrowed coronary arteries that supply oxygenated blood to the heart muscle. There is a shortage of study of bachelor students. The goal of this research was directed to assess level of patient’s information toward some modifiable risk factors of IHD at Rania teaching hospital in Kurdistan region of Iraq during the period of (20th October 2019 - 10th February 2020). A non- probability purposive sample of (143) patients; the study instrument was constructed of total (42) items for the purpose of data collection. The content validity of the instrument was determined through a panel of (12) experts. Reliability of the instrument was determined through the use of internal consistency reliability (split half) approach which was estimated as r = (0.83) the data were collected through the use of interview technique (face to face approach), the computer files is used to organizing and coding it. The data analyzed by Statistical approaches which includes: descriptive and inferential statistical and chi- square, data analysis (SPSS version 25). The outcome showed that most of the sample rang from the age (25-40) years and most of them were male from urban, more than half of them were unemployed but nearly half of them were graduated from primary school. 32.2% of them diagnosed by cardiovascular disease. However more than half of them had a high level of information about IHD as a general, and the TV was the first source of their information but more than half of them were overweight, 65% did not do regular exercise, 52.4% were relatively stressful. Also, the study demonstrated that there is no significant association between socio demographic data and level of patient’s information toward some modifiable risk factors of IHD, with age, gender, educational level and occupation with IHD, at p value greater than 0.05. The study recommended to ministry of health and directorate of health in Rania city to develop and supervise the center of dietary regimen and halls of exercise for the people to implement their information and practice it